Student Awareness, Utilization, and Satisfaction with Guidance and Counseling Services in Indonesian High Schools - Wangid, Muhammad Nur; Sari, Widya Juwita; Pratiwi, Chici; Atmoko, Adi (SCAD Independent, 2025)
This study investigated Indonesian high school students’ perceptions of school Guidance and Counseling (GC) services, focusing on three interrelated dimensions: awareness, utilization, and satisfaction. While GC services are recognized as essential for supporting student development, limited research has comprehensively examined how they are perceived and accessed by students themselves. Using a cross-sectional survey design, data were collected from 578 Grade 11 and 12 students in public senior high schools in Yogyakarta. Instruments adapted from Gallant and Zhao were employed, with reliability scores of α = 0.716 (awareness), α = 0.916 (utilization), and α = 0.951 (satisfaction). Statistical analyses included percentage distributions, Pearson chi-square, Mantel-Haenszel chi-square, and ordinal logistic regression. Findings revealed that although students demonstrated high awareness of GC services, variations in utilization and satisfaction were evident across grade levels. Notably, while higher awareness was associated with greater satisfaction, more frequent use was linked to lower satisfaction, indicating a potential mismatched between student expectations and the quality of services provided. These results highlighted the need for student-centered and developmentally responsive counseling services, offering implications for both national policy and international educational practices.